Zika virus infection: epidemiology, clinical manifestations and diagnosis. Issue 5 (October 2016) - Calvet, Guilherme Amaral; Santos, Flavia Barreto dos; Sequeira, Patricia Carvalho
Abstract : Purpose of review: Zika virus (ZIKV) is an arbovirus previously believed to cause only a mild and self-limiting illness. Recently, it has emerged as a new public health threat that caused a large outbreak in French Polynesia in 2013–2014 and since 2015 an explosive outbreak in Brazil, with an increase in severe congenital malformations (microcephaly) and neurological complications, mainly Guillain–Barré syndrome (GBS). Since then, it has spread through the Americas. On 1 February 2016, the WHO declared the ZIKV epidemic in Brazil a Public Health Emergency of International Concern. We reviewed the epidemiology of ZIKV infection, clinical presentations and diagnosis. We highlighted the clinical features and nonvector borne transmission of the virus. Recent findings: Association between ZIKV infection and severe foetal outcomes, including microcephaly and other birth defects; increased rate of GBS and other neurological complications due to the ongoing ZIKV outbreak; increased evidence to date of ZIKV being the only arbovirus linked to sexual transmission; the challenge of ZIKV diagnosis; and the need for a specific point-of care test in epidemic scenarios. Summary: The findings illustrate the emergence of a viral disease with the identification of new associated disorders, new modes of transmission, including maternal–foetal and sexual transmission.